1995
DOI: 10.1080/10256019508036256
|View full text |Cite
|
Sign up to set email alerts
|

Trophic Levels and Anomalous δ15N of Insects on Raspberry (Rubus Idaeus L.)

Abstract: Unexpectedly elevated 615N values (8 to 1@A,) were found in adult raspberry beetles (Byturus tomentosus), collected shortly after emergence from over-winteringsites. Elevated S1'N values (1 1 to 14%, ) were also found in over-wintered larvae, but young adults, collected shortly after metamorphosis in autumn, and larvae collected from raspberry drupelets and receptacles in summer, did not show such elevated 6"N. S' 5N values of feeding larvae ( -2%,) were close to those of their food plant, red raspberry (Rubus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 29 publications
5
64
0
Order By: Relevance
“…The result was similar to the green peach aphid, Myzus persicae, which was more than 6‰ depleted in 15 N relative to their hosts (cabbage seedlings) (Wilson et al, 2011). Aphids are plant sap-feeding insects, which have been frequently reported as showing no enrichment or even depletion in 15 N relative to their diet (McCutchan et al, 2003;Sagers and Goggin, 2007;Schumacher and Platner, 2009;Scrimgeour et al, 1995). The mechanism governing nitrogen stable isotopic trophic differences between the Dd 15 N of P. japonica adults to cotton aphids (6.0‰ or 7.2‰) and those of P. japonica adults to maize aphids (0.3‰ or À0.2‰) remains unclear.…”
Section: Prey Origins Of Predatory Beetlessupporting
confidence: 52%
“…The result was similar to the green peach aphid, Myzus persicae, which was more than 6‰ depleted in 15 N relative to their hosts (cabbage seedlings) (Wilson et al, 2011). Aphids are plant sap-feeding insects, which have been frequently reported as showing no enrichment or even depletion in 15 N relative to their diet (McCutchan et al, 2003;Sagers and Goggin, 2007;Schumacher and Platner, 2009;Scrimgeour et al, 1995). The mechanism governing nitrogen stable isotopic trophic differences between the Dd 15 N of P. japonica adults to cotton aphids (6.0‰ or 7.2‰) and those of P. japonica adults to maize aphids (0.3‰ or À0.2‰) remains unclear.…”
Section: Prey Origins Of Predatory Beetlessupporting
confidence: 52%
“…In this analysis, adult aquatic insects were excluded because the metamorphosis of insects from larvae/nymphs into adults is known to greatly increase the δ 15 N value (Scrimgeour et al 1995). The result indicated that stream macroinvertebrates with lower δ 13 C values tended to show lower δ 15 N values (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…However, important exceptions exist. Fluidfeeders, a group that includes blood-feeding parasites and hempiteran insects (2), frequently have been found to deviate from these typical patterns such that fluid-feeders are usually reported as showing no enrichment or even depletion in 15 N relative to their diet (2,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Although it is now commonly accepted that fluid-feeders deviate from typical patterns of enrichment, these observations have stimulated considerable speculation (2,14,18) but little, if any, research targeted at explaining the mechanistic basis of such atypical patterns of nitrogen enrichment.…”
mentioning
confidence: 99%